2017
DOI: 10.18632/oncotarget.18134
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin plays a key role in retinal neuropathy prior to endothelial damage in diabetic mice

Abstract: Diabetes is a chronic metabolic syndrome that results in changes in carbohydrate, lipid and protein metabolism. With diabetes for a long time, it increases the risk of diabetic retinopathy (DR) and long-term morbidity and mortality. Moreover, emerging evidence suggests that neuron damage occurs earlier than microvascular complications in DR patients, but the underlying mechanism is unclear. We investigated diabetes-induced retinal neuropathy and elucidated key molecular events to identify new therapeutic targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…Several studies have shown that the decline of Trx expression was found in the development of many diseases including Parkinson's disease (PD), sepsis [13], age-related cataract [14] and DR. In our previous study, we also found that decreased Trx expression plays a key role in retinal neurodegeneration prior to endothelial damage in diabetic mice [15].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Several studies have shown that the decline of Trx expression was found in the development of many diseases including Parkinson's disease (PD), sepsis [13], age-related cataract [14] and DR. In our previous study, we also found that decreased Trx expression plays a key role in retinal neurodegeneration prior to endothelial damage in diabetic mice [15].…”
Section: Introductionmentioning
confidence: 72%
“…We also found that it can delay retina degeneration occurrence after Sulforaphane (SF), Lycium barbarum polysaccharides and grape seed proanthocyanidin extract treatment through up-regulating the expression of Trx in vitro and in vivo [15][16][17]. Moreover, Previous studies have shown that SF can up-regulate Trx [18] and that SF treatment inhibits retinal degeneration in Tubby mice [19].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Because retinal fluid handling is not conserved in diabetic retinas (Berkowitz et al, 2012; Pannicke et al, 2006), the discrepancy between our MRI and histological values may also be attributed to differences in the dehydration process between eyes that were dissected prior PFA fixation in histology procedures, but not in MRI. Furthermore, histological examination has produced inconsistent results with thicknesses that are unchanged (Ganapathy et al, 2009; Martin et al, 2004) or reduced (Ren et al, 2017) at 4-5 weeks after onset of diabetes. At longer periods of diabetes, retinal thinning (Li et al, 2010; Martin et al, 2004; Ozaki et al, 2018; Qian et al, 2018; Sachdeva et al, 2018; Yang et al, 2018; Zheng et al, 2007) or thickening (Berkowitz et al, 2009; Li et al, 2013) has been observed.…”
Section: Discussionmentioning
confidence: 99%